Association of Diligence and Sociability with Stroke: A UK Biobank Study on Personality Proxies - Markus J. T. de Ruijter; Amelia D. Dahlén; Gull Rukh; Helgi B. Schiöth (Frontiers in Bioscience-Landmark, 2022)
Background: There is a growing interest in how personality may be related to the risk of developing disease. Associations between personality and stroke have so far only been studied in relation to stroke mortality. However, many stroke survivors suffer severe impairment of quality of life due to sequelae such as aphasia, hemiparesis, depression and anxiety. In this study we assess the association between personality and risk of stroke, regardless of mortality. Methods: Using self-reported data on psychological factors, mental health and social support, proxies for the Big Five personality traits were developed for 482,535 participants in the UK Biobank. Logistic regression and Cox proportional hazard models, with 95% confidence intervals (CI), were used to estimate odds ratios (OR) and hazard ratios (HR) between each personality trait and stroke prevalence (N = 6793) and incidence (N = 3312), respectively. Models were adjusted for demographic, health-related, and lifestyle factors. Results: Diligence and sociability were associated with a lower risk of stroke incidence in the fully adjusted model (respectively: [HR = 0.92; 95% CI = (0.88, 0.96)], [HR = 0.93; 95% CI = (0.89, 0.97)]). However, nervousness, curiosity and warmth were not significantly associated with a risk of stroke incidence. Conclusions: Individuals with higher levels of diligence and sociability may be at a reduced risk of developing stroke. With respect to the debated role of neuroticism in relation to cardiovascular disease, we did not find evidence of an association between nervousness and risk of developing stroke.